2022
DOI: 10.1029/2022jg006889
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Freeze‐Thaw History on Soil Carbon Response to Experimental Freeze‐Thaw Cycles

Abstract: Freeze-thaw cycles are a deformation process that shape soil function in warming permafrost landscapes and represent an intrinsic component of thaw (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
(124 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, our study found that the daily average Rs flux during IFP was relatively low compared to those in DFP and SMP, indicating that the non-growing-season soil CO 2 emissions via Rs were mainly concentrated in DFP and SMP. We also observed a significant increase in Rs after soil thawing, which was in line with previous findings [44][45][46]. The pattern of increased Rs after soil thawing during SMP may reflect the emergence of suitable abiotic or biotic conditions favorable for microbial and root respiration at the end of winter, such as appropriate soil temperature and moisture, restoration of the growth of plant roots [44,47], as well as increased soil microbial activity [44,46].…”
Section: Soil Respiration Under Different Snow Cover Treatmentssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, our study found that the daily average Rs flux during IFP was relatively low compared to those in DFP and SMP, indicating that the non-growing-season soil CO 2 emissions via Rs were mainly concentrated in DFP and SMP. We also observed a significant increase in Rs after soil thawing, which was in line with previous findings [44][45][46]. The pattern of increased Rs after soil thawing during SMP may reflect the emergence of suitable abiotic or biotic conditions favorable for microbial and root respiration at the end of winter, such as appropriate soil temperature and moisture, restoration of the growth of plant roots [44,47], as well as increased soil microbial activity [44,46].…”
Section: Soil Respiration Under Different Snow Cover Treatmentssupporting
confidence: 90%
“…The pattern of increased Rs after soil thawing during SMP may reflect the emergence of suitable abiotic or biotic conditions favorable for microbial and root respiration at the end of winter, such as appropriate soil temperature and moisture, restoration of the growth of plant roots [44,47], as well as increased soil microbial activity [44,46]. In addition, the surge in Rs from thawed soil at the end of the non-growing season may also be caused by the rapid release of carbon dioxide stored in soil during the freezing period after the melting of the ice layer [45,48].…”
Section: Soil Respiration Under Different Snow Cover Treatmentsmentioning
confidence: 99%
“…One possible reason is that in the permafrost studied by Payandi-Rolland et al (2021), the microbial communities are resistant to FTCs. Previous studies reported that the microbes in a variety of soil types are highly susceptible to the first freeze-thaw cycle, and then less affected by subsequent freeze-thaw cycles (Koponen et al, 2006;Song et al, 2017;Patel et al, 2021;Rooney et al, 2022). The different climate regions and peatland types (temperate fen grasslands vs. permafrost bogs) may be responsible for the different changes in DOC concentrations after FTCs.…”
Section: Impact Of Freeze-thaw Cycles On Flow Rates Dissolved Organic...mentioning
confidence: 99%
“…Consequently, it is imperative to consider the significant impact of freeze–thaw cycles (F-Ts) on the mechanical performance and durability of CGC. Extensive research has been conducted on the deterioration patterns of CGC under F-Ts conditions, elucidating the macroscopic mechanical effects of F-Ts on CGC [ 27 , 28 , 29 ]. Under F-Ts conditions, concrete materials undergo two main changes.…”
Section: Introductionmentioning
confidence: 99%